STUDI BUDAYA NONMATERIAL WARGA JATON - Suzy Azeharie; Sinta Paramita; Wulan Purnama Sari (Asosiasi Pendidikan Tinggi Ilmu Komunikasi (ASPIKOM), 2019)
Jaton village is situated in the heart of where the majority of the population is Christian. For hundreds of years the residents of Jaton Village lived side by side in harmony with the majority of Minahasa tribes who had different religions. A long historical factor makes Jaton Village unique because residents of Jaton Village are direct descendants of Kyai Modjo, a religious teacher from Prince Diponogoro, who was banished by Dutch colonialists along with 63 of his followers to the Tondano area in 1828. Amid the increasing number of violence committed by one religious group in another religion, this research is aim to see a form of nonmaterial culture in Jaton society. This research will answer the question of what form of non-material cultures includes values, norms and regulations for the people of Jaton Village, and how are the values, norms and beliefs passed on to the next generation. The method used is qualitative with case study approach through observation and in-depth interview. The results showed that the Jaton community still holds an ancestral culture originating from Java. In addition, the norms created are mixed up, so there is no norm that limits behavior or action. However, the most obvious thing to hold firmly is the norm of Islamic teachings which is their belief.